Legal procedures and foreign restrictions on conducting a merger and acquisition (M&A) transaction in the vietnamese laws - Than, Thu Thao (2020)
Vietnam continues to attract foreign investment. Apart from via direct investment, the foreign investors also achieve market access by way of M&A, both onshore in Vietnam and offshore when there are existing foreign investors. However, during the formulation of the deal structure, parties often overlook the closing and post-closing steps, which contain significant risks from both legal and financial perspective. Having a roadmap for the transaction at an early stage will prepare a potential purchaser for what to expect during a transaction. If the proposed structure does not work, then be flexible in considering alternatives. The Thesis will point out a typical “roadmap” for investors, especially foreign investors to carry out an M&A transaction, including legal procedures and notices of legal framework restriction in Vietnam